Scavi e ricerche a Calvatone romana: il “Quartiere degli Artigiani” (scavi 2005 - 2007) (LANX. Journal of the Scuola di Specializzazione in Beni Archeologici - Università degli Studi di Milano, 2009)
The archaeological excavations – organized by the University of Milano in the years 2005-2007 – in the vicus of Calvatone-Bedriacum brought to the identification of a large building probably used to productive function and for this reason called “Craftsmen Quarter”. The excavations, still in progress, have found few small rooms, with no rich ornament, probably shops or stores.
Keywords: Calvatone; Bedriacum; vicus; archaeological excavations; productive buildings; GIS